NUMERACY INTRODUCTION STRATEGIES FOR CHILDREN AGED 3-4 YEARS - Syarifatunnida, Rizka; Sahrul, Sahrul; Kusbiantari, Dyah; Maghfiroh, Hidayah Rosanti; Aini, Nur; Mustafida, Siti Fatimatul; Hidayah, Deva Nur; Yunus, Muhammad (Universitas Al-Hikmah Indonesia, 2024)
Amid the low average literacy levels among students in Indonesia, it becomes essential to introduce various numeracy strategies from an early age. This study aims to understand the different numeracy introduction strategies for children aged 3-4 years at Kelompok Bermain Islam (KBI) Riyadl, an Islamic school focused on developing independence, interest, and capabilities of early childhood. The research employs a case study approach with observations conducted over at least three months, involving 15 children in group B1 as subjects. Data collection techniques include participant observation, interviews with parents, and documentation. Triangulation is conducted by comparing observation results with interviews or vice versa. This study concludes that educators at KBI Riyadl have introduced various innovative strategies that effectively stimulate and develop the basic numeracy interest and skills of early childhood children. The variety of numeracy activities and games, along with the intensity and closeness built by educators with the students, are significant factors in the success of introducing numeracy to young children. Additionally, the abilities and improvisation of educators, as well as the strategy of having double educators, contribute to achieving optimal numeracy introduction goals. However, this study has limitations, as it did not observe differences in numeracy introduction strategies when applied to different biological genders of students, between boys and girls. Therefore, it cannot be determined whether the impact is the same or different. The study also recommends the proactive role of parents in accompanying the introduction of numeracy to early childhood for more optimal results.